Regulating Fibrocartilage Stem Cells via TNF-α/Nf-κB in TMJ Osteoarthritis. (March 2022) - Bi, R.; Chen, K.; Wang, Y.; Luo, X.; Li, Q.; Li, P.; Yin, Q.; Fan, Y.; Zhu, S.
In this study, we investigate harnessing fibrocartilage stem cell (FCSC) capacities by regulating tumor necrosis factor α (TNF-α) signaling for cartilage repair in temporomandibular joint osteoarthritis (TMJOA). Stem cell specifics for FCSCs were characterized in the presence of TNF-α. Etanercept as a TNF-α inhibitor and BAY 11-7082 as an Nf-κB inhibitor were used to study TNF-α regulation of FCSCs. Lineage tracing was performed in Gli1-CreERT + ;Tm fl/fl mice when etanercept (1 mg/kg, every 3 d) or isometric vehicle was subcutaneously injected to trace specific changes in FCSCs. Surgically induced TMJOA Sprague-Dawley rats were generated with BAY 11-7082 (5 mg/kg, every 3 d) or vehicle subcutaneous injection to investigate the functional role of TNF-α/Nf-κB in TMJOA. Anterior disc displacement (ADD) rabbits were used to analyze the therapeutic effect of etanercept as a TMJOA intra-articular treatment with etanercept (0.02 mg in 100 μL, every 2 wk) or isometric vehicle. In vitro, TNF-α inhibited proliferation of FCSCs and increased FCSC apoptosis. TNF-α activation interfered with osteogenic and chondrogenic differentiation of FCSCs, while etanercept could partially recover FCSC specificity from TNF-α. FCSC lineage tracing in Gli1-CreERT + ;Tm fl/fl mice showed that the chondrogenic capacity of Gli1 + cell lineage was markedly suppressed in osteoarthritis cartilage, the phenotype of which could be significantly rescued by etanercept. Specifically blocking the Nf-κB pathway could significantly weaken the regulatory effect of TNF-α on FCSC specificity in vitro and in TMJOA rats in vivo. Finally, intra-articular etanercept treatment efficiently rescued TMJ cartilage degeneration and growth retardation in ADD rabbits. Inhibition of TNF-α signaling reduced Nf-κB transcripts and recovered FCSC specificities. In vivo, etanercept treatment effectively rescued the osteoarthritis phenotype in TMJOA mice and ADD rabbits. These data suggest a novel therapeutic mechanism whereby TNF-α/Nf-κB inhibition promotes FCSC chondrogenic capacity for cartilage transformation in TMJOA.